Adjusting Your Dreams? The Effect of School and Peers on Dropout Behaviour - Dominique Goux; Marc Gurgand; Eric Maurin (Institute for the Study of Labor (IZA), 2014)
At the end of middle school, many low achieving students have to abandon hope of getting into selective high-school programs, which may be a source of disappointment and eventually lead them to dropout from high-school. Based on a randomized controlled trial, this paper shows that low-achieving students' aspirations can be made more realistic through a series of meetings facilitated by the school principals and that more realistic aspirations are followed by a significant reduction in grade repetition and high-school dropout. Building on detailed information on friendship networks within classes, we also find evidence that improved outcomes in treated classes encompass improved social interactions between low achieving students and their high achieving classmates.
Keywords: I21; I24; J18; 330; school dropout; tack choices; school aspiration; social networks